2021
DOI: 10.3390/pharmaceutics13070931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protoberberine-Rich Fraction of Chelidonium majus L. on Endometriosis Regression

Abstract: Endometriosis is a gynecological disease defined by the presence of endometrial tissue outside the uterus. To date, the effective treatment of this disease is still based on invasive surgery or laparoscopy. Chelidonium majus L. (Papaveraceae) belongs to medicinal, latex-bearing plants. Extracts from the plant are a rich source of pharmacologically active agents. Protoberberine compounds derived from C. majus possess anticancer and antiproliferative activities. In the present study of a rat model of endometrios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…By interfering with these signaling pathways, berberine may help regulate cellular processes and inhibit the growth and invasiveness of endometriotic lesions (Z. Gaurav et al, 2020;Gautam, 2022;Gu & Zhou, 2021;Warowicka et al, 2021;Zhou & Zhou, 2011).…”
Section: Phytochemicals Reported For Management Of Endometriosismentioning
confidence: 99%
“…By interfering with these signaling pathways, berberine may help regulate cellular processes and inhibit the growth and invasiveness of endometriotic lesions (Z. Gaurav et al, 2020;Gautam, 2022;Gu & Zhou, 2021;Warowicka et al, 2021;Zhou & Zhou, 2011).…”
Section: Phytochemicals Reported For Management Of Endometriosismentioning
confidence: 99%
“…Microbiota and associated factors seem important for the G-E origin and the growth of endometriosis [ 6 ]. This could explain the effect of food intake [ 28 , 29 , 30 ] and exercise [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ] on endometriosis and of food supplements such as berberine [ 38 , 39 ], NAC [ 40 ], zinc [ 36 , 37 ] and gluten-free diet [ 41 ].…”
Section: New Understanding Of Pathophysiologymentioning
confidence: 99%
“…Berberine indirectly improved IR, regulated hormone secretion and increased ovulation and conception rates in PCOS patients mainly by reducing the relative abundance of polysaccharide flora, increasing the relative abundance of SCFAs producing flora and reducing endotoxemia (Wang T. et al, 2017). Additionally, berberine inhibited the relapse of EMs by affecting the concentration of metabolites involved in energy homeostasis such as glucose, glutamine and lactate (Warowicka et al, 2021). Several studies have suggested that the mechanism of action of berberine in reducing HA and hyperinsulinemia in PCOS model rats may be related to the promotion of SCFAs production by inhibiting the LPS/NF-κB signaling pathway, increasing the relative abundance of beneficial intestinal bacteria and decreasing the relative abundance of pathogenic bacteria Shen et al, 2021).…”
Section: Active Ingredients Of Chinese Herbal Medicinesmentioning
confidence: 99%